2019
DOI: 10.1108/dlo-11-2018-0154
|View full text |Cite
|
Sign up to set email alerts
|

Design thinking for improving employee experience: a case of a food tech company

Abstract: Purpose The purpose of this paper is to demonstrate applicability of design thinking in creating employee centric HR solutions. This application is studied in the context of a food tech company. A design thinking process for arriving at an HR solution for employee experience management is proposed. Design/methodology/approach The study uses a single case study method. The HR professionals of a food tech company were interviewed to relate their narratives with the existing conceptual framework on design think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…India ranks 7th on the list of top 10 contributions made by Nations. Researchers such as Panneerselvam and Balaraman (2022), Yadav and Vihari (2021), Sinha et al (2020), Soni et al (2017) and Tymon et al (2010) found a lack of work in EE in the Indian context. Thus, further research can promote contributions made by Asian countries, and additionally, collaborative research between Western and Asian countries can be done.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…India ranks 7th on the list of top 10 contributions made by Nations. Researchers such as Panneerselvam and Balaraman (2022), Yadav and Vihari (2021), Sinha et al (2020), Soni et al (2017) and Tymon et al (2010) found a lack of work in EE in the Indian context. Thus, further research can promote contributions made by Asian countries, and additionally, collaborative research between Western and Asian countries can be done.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Because organisations are striving to stay competitive in the post-pandemic world, a need to redefine EX is a business necessity as employers worldwide are experiencing “the great resignation”. Knowing what align, empower and accelerate business impact, understanding people needs and preferences – including how and where they want to work, as well as what they need to feel productive – and then initiate action on those expectations (Sinha et al , 2020) are critical for leveraging organisational human capital. EX is emerging as the new employee value proposition (EVP).…”
Section: Employee Experience In the Never Normal Agementioning
confidence: 99%
“…Most importantly, this study digs in to find the business context, pressures and functional capabilities in the employee agility context, firstly, from which we recommend how human resource management and development practice should be designed to drive workforce agility. Our approach is closer to “design thinking” practiced in HR, where managerial or employee work experience can be heard in a business context to build better HR solutions (Sinha et al , 2019; Ulrich et al , 2009). For this reason, qualitative research is the most appropriate way to inductively explore the experiences (Corbin and Strauss, 2008) and then build comprehensive frameworks for both workforce agility and SHRM practice for HR managers.…”
Section: Introductionmentioning
confidence: 99%